Israeli visit – An Experience - Ningoji, Santosh Nagappa; Mudalagiriyappa, Mudalagiriyappa; C, Seenappa (Indian Farming, 2021)
India, an agrarian country, hasbeen facing various challenges inrecent years - lower productivity,resource crunch and erratic weather,all of these leading into lower returns.Hence, our Country should userecent technologies viz., efficientirrigation technologies (dripirrigation and mini sprinklers),protected cultivation high valuecrops, community farming andcommunity dairy to uplift theagriculture and livelihood of farmers.